Business processes monitoring by means of real-time visual dashboards - Batyuk, Anatoliy; Voityshyn, Volodymyr (Видавництво Львівської політехніки, 2017)
For modern enterprise IT ecosystems it is crucial to monitor business processes in near real-time mode using powerful visualization capabilities. The implemented by the authors distributed system is based on Elastic Stack platform which ensure its scalability and high availability. The designed solution architecture offers opportunities to gain further useful insight into the collected event data employing machine-learning techniques.
Keywords: business process management; BPM; BPMS; BPMN; business process; event data; process logs; Elasticsearch; Kibana